Online Political Branding of Presidential Candidates: A Comparison of Ganjar Pranowo and Anies Baswedan in Indonesia’s 2024 Election - Fatikha, Nindya Tiara; Suranto, Suranto (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2024)
Ahead of the impending 2024 Presidential Election, the topic of presidential candidates was frequently debated in all Indonesian media. Ganjar Pranowo and Anies Baswedan were political actors who planned to run in the 2024 presidential election. Both of them utilized Twitter to foster political discussion while expanding their fame. This study uses a descriptive qualitative approach and the Nvivo 12Plus program to compare Ganjar Pranowo's and Anies Baswedan's political branding in developing political communication ahead of the 2024 Presidential Election on Twitter. The comparison of political branding is based on looks, personality, and significant political messages. The findings suggest that Ganjar Pranowo and Anies Baswedan used their Twitter accounts to conduct vast and extensive political branding campaigns. Ganjar Pranowo and Anies Baswedan scored the highest on the appearance indication for dress style. Ganjar Pranowo demonstrated personality by succeeding in the importance of public relations, whilst Anies Baswedan did so through his speaking manner. Ganjar Pranowo's major political message emphasized the value of desire, whilst Anies Baswedan emphasized the value of achievement.